PROPOSTA DE SEQUÊNCIA DIDÁTICA PARA O ENSINO DE ONDULATÓRIA: VÍDEOS E ATIVIDADES COMO POTENCIALIZADORES DA APRENDIZAGEM - MOREIRA, Evaldo Gilberto (2024)
One of the main difficulties we encounter in high school, with the Physics subject, is how to teach so that students are encouraged to learn and develop their learning autonomously. From this perspective, we verified evidence of significant learning in a methodological approach to teaching wave content. The methodological procedure adopted in this research consists of the elaboration of a Didactic Sequence. For the theoretical foundation regarding the process of investigating student learning, it was based on David Ausubel's theory of meaningful learning (2003). The sequence was applied at a public school in the city of Pinheiro – MA. The survey of data obtained in the research shows that the proposed methodology provides a significant improvement in learning.